Active films based on bio-polyethylene and natural extracts rich in tocopherols for food packaging applications - Mellinas, A. C.; García-Serna, E.; Jiménez, A.; Garrigós, M. C. (Frontiers in Materials, 2024)
Antioxidant/antifungal active films based on bio-polyethylene (BPE) added with Nutrabiol ® T90 and Tocobiol ® Plus natural extracts rich in tocopherols at different concentrations (1 and 3 wt%) were developed by melt-blending followed by compression-molding. Thermal, barrier, mechanical, optical and functional properties of the developed active films were evaluated. The addition of active extracts did not cause important changes in thermal and barrier properties of active films whereas a significant increase in oxidative stability was found. Release kinetics of active additives migration showed higher tocopherol diffusion coefficient and antioxidant capacity, determined by the DPPH and ABTS methods, for films containing 3 wt% of Nutrabiol ® T90. This film also delayed polymer oxidation in 260 min and extended strawberries shelf-life during storage for 7 days compared to neat BPE, showing a significant antifungal effect. The studied biomaterials offer great potential to substitute conventional petrol-derived materials at the industrial scale as active food packaging systems to increase the shelflife of perishable foodstuff.